Effect of Free-Range Chicken Eggs on Perineal Wound Healing among Postpartum Women - Hastuti Usman; Muliani Muliani; Niluh Nita Silfia; Sarliana Sarliana (EMBRIO: Jurnal Kebidanan, 2023)
10percent of maternal mortality during the postpartum period are caused by infection due to bleeding from tears in the birth canal (perineal wound). The wound healing process is influenced by the intake of protein-rich nutrients. Free-range chicken eggs from are a high source of protein (Komala, 2021). This study aims to determine the effect of free-range chicken eggs on perineal wound healing among postpartum women. This was a pre-experimental study with intact group comparison. There were 32 samples who were selected using purposive sampling technique. The samples were assigned into the Intervention Group (administered with free-range chicken eggs) and the Control Group (were not administered with free-range chicken eggs). Data collection was performed through direct observation of perineal wounds using the REEDA scale score. Data were analyzed using the Fisher Exact statistical test. The results showed that there was a faster wound healing process among respondents who were administered with free-range chicken eggs (81.2percent) compare to those who were not administered with free-range chicken eggs (25percent) with a p value of 0.002 less than 0.05. It can be concluded that the administration of free-range chicken eggs chicken eggs had an effect on perineal wound healing among postpartum women. It is expected that postpartum women who experience perineal wound starting from the second grade will consume boiled free-range chicken eggs to speed up the wound healing process.